The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/2055102917719563
|View full text |Cite
|
Sign up to set email alerts
|

An examination of college student wellness: A research and liberal arts perspective

Abstract: Promoting wellness within academia reduces disease frequency and enhances overall health. This study examined wellness factors among undergraduate students attending a research university (n = 85) or a small liberal arts college (n = 126). Participants were administered surveys which measured physical, emotional, social, intellectual, and occupational wellness. Significant institutional differences emerged on measures of physical and social wellness. When collapsed across academic institutions, students who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 67 publications
4
34
1
2
Order By: Relevance
“…One study demonstrated an increase in students' level of wellness with class standing (Oleckno & Blacconiere, 1990), while others noted a decline in nutrition and stress management during the first year (LaFountaine et al, 2006). Another showed students attending a liberal arts college were more physically active, compared to those attending a research college (Baldwin et al, 2017); however, the researchers note that these findings could be attributed to gender.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…One study demonstrated an increase in students' level of wellness with class standing (Oleckno & Blacconiere, 1990), while others noted a decline in nutrition and stress management during the first year (LaFountaine et al, 2006). Another showed students attending a liberal arts college were more physically active, compared to those attending a research college (Baldwin et al, 2017); however, the researchers note that these findings could be attributed to gender.…”
mentioning
confidence: 82%
“…These units offer frequent events tailored to specific subpopulations (e.g., year of study, gender, sexual orientation), on a particular health topic (e.g., smoking, vaping, drinking). The programs are designed to improve students' physical and mental health (Slavin, Schindler, & Chibnall, 2014), promote psychosocial and stress management techniques (Conley, Travers, & Bryant, 2013), decrease depression and anxiety (Dvořáková et al, 2017), and develop positive health behaviors to enhance students' quality of life (Baldwin, Towler, Oliver, & Datta, 2017). For example, participation in a mindfulness-based program has been shown to increase first-year college students' life satisfaction, and decrease their depression and anxiety (Dvořáková et al, 2017).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Noticeably, discourses of SM user are also on health. As cited by [31], students reported that stress and sleep difficulties negatively impacted their academic performance. Moreover, many college students engage themselves in unhealthy behaviours, making them at risk for developing serious problems in health in the future.…”
Section: Discourse Of Hei Stakeholdersmentioning
confidence: 93%